War or peace? The possible scenarios of colonising Mars. (November 2017) - Szocik, Konrad; Wójtowicz, Tomasz; Baran, Leszek
Abstract: The idea of the manned mission to Mars and Mars colonising is getting more reliable and realistic. However, it is not clear if one country could realize such great economic, societal, and technological challenge. Here we show what are possible chances and obstacles for the international collaboration in the future space policy that is focused on launching the manned mission to Mars. We discuss some peculiarities appropriate for peaceful and conflict scenarios of the planned colonisation of Mars.